Arabic for Specific Purposes in Malaysia: A Literature Review - Abdul Ghani, Mohammad Taufiq; Wan Daud, Wan Ab Aziz; Ramli, Saipolbarin (Issues in Language Studies, 2019)
Many universities have introduced Arabic language for specific purpose courses in order to help learners master the terminologies and language patterns used in specific fields. This paper reviews the rising popularity of learning Arabic for specific purposes among Malaysian students in light of a more contemporary needs than decades ago when the Arabic language is learnt mainly for religious purposes. The qualitative approach has been adopted in conducting this literature review. This review provides inputs to help create a module for teaching Arabic for specific purposes. This study has a significant contribution to the field of Arabic teaching in Malaysia as it informs practitioners and researchers on how to improve the effectiveness of Arabic for specific purpose courses to help students gain academic and career advantages in the long run.